2005
DOI: 10.1002/art.21149
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus in a multiethnic US cohort (LUMINA): XXV. Smoking, older age, disease activity, lupus anticoagulant, and glucocorticoid dose as risk factors for the occurrence of venous thrombosis in lupus patients

Abstract: Objective. Venous thrombosis is a relatively frequent and serious complication in systemic lupus erythematosus (SLE) that has been associated with the presence of antiphospholipid antibodies (aPL). However, venous thrombotic events can also be seen in patients without aPL, and only a few patients with aPL develop venous thrombosis. This study was carried out to ascertain other factors contributing to the development of venous thrombosis in SLE.Methods. Patients with SLE, ages >16 years with <5 years disease du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 47 publications
(37 reference statements)
2
79
0
4
Order By: Relevance
“…In our study, 1 episode of thrombosis was observed among every 28 women who received menopause hormonal therapy. Avoiding menopause hormonal therapy in women who are positive for aPL would not be enough, since other factors, such as smoking, older age, disease activity over time, and glucocorticoid dose, are also associated with the occurrence of venous thrombosis in lupus patients (42). Therefore, we consider the real threat of menopause hormonal therapy in women with SLE to be the risk of developing thrombosis, not the effect of menopause hormonal therapy on disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 1 episode of thrombosis was observed among every 28 women who received menopause hormonal therapy. Avoiding menopause hormonal therapy in women who are positive for aPL would not be enough, since other factors, such as smoking, older age, disease activity over time, and glucocorticoid dose, are also associated with the occurrence of venous thrombosis in lupus patients (42). Therefore, we consider the real threat of menopause hormonal therapy in women with SLE to be the risk of developing thrombosis, not the effect of menopause hormonal therapy on disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether GC also contributed to his thrombosis. However, data from Cushing's syndrome patients, anecdotal evidence of thrombosis after GC, and limited evidence from a lupus cohort study may support such a possibility (18,45,46). It may be prudent to try to initiate high-dose GC therapy, or at least pulse GC, only after initiation of anticoagulation therapy in patients with CAPS/probable CAPS, and thereafter make an effort to taper the dose of GC as fast as the clinical condition would allow.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive evaluation revealed elevated inflammatory markers, including erythrocyte sedimentation rate (ESR; 102 mm/hour), C-reactive protein level (56 mg/liter), positive antinuclear antibodies (ANAs; Ͼ1:640), strongly positive anti-doublestranded DNA (anti-dsDNA) titers, low levels of C4 (9 mg/dl, normal range 16 -38), prolonged prothrombin time (16.2 seconds, normal range 10 -13), prolonged activated partial thromboplastin time (60 seconds, normal range [27][28][29][30][31][32][33][34][35][36][37][38], and positive lupus anticoagulant (LAC) by dilute Russell's viper venom time. His urine analysis showed proteinuria (0.440 gm protein/gm creatinine), hematuria (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) …”
Section: History Of the Present Illnessmentioning
confidence: 99%
“…12 aPLs were strongly associated with thrombosis in this cohort. In the LUMINA Study, 9% of SLE patients had at least one VT. 13 VT was independently associated with LAC and several other risk factors (smoking, older age, disease activity, and glucocorticoid dose).…”
Section: Apls and Risk Of Thrombosismentioning
confidence: 93%